2021
DOI: 10.1038/s41467-021-24186-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic transmissivity inferred from ice-sheet relaxation following Greenland supraglacial lake drainages

Abstract: Surface meltwater reaching the base of the Greenland Ice Sheet transits through drainage networks, modulating the flow of the ice sheet. Dye and gas-tracing studies conducted in the western margin sector of the ice sheet have directly observed drainage efficiency to evolve seasonally along the drainage pathway. However, the local evolution of drainage systems further inland, where ice thicknesses exceed 1000 m, remains largely unknown. Here, we infer drainage system transmissivity based on surface uplift relax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…2021; Lai et al. 2021). These observations are more consistent with the assumption of a pinned contact line during the drainage process, as made in Case (ii) of the droplet drainage model.…”
Section: Final Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…2021; Lai et al. 2021). These observations are more consistent with the assumption of a pinned contact line during the drainage process, as made in Case (ii) of the droplet drainage model.…”
Section: Final Remarksmentioning
confidence: 99%
“…It is also of interest to note that in the analogue problem of fluid drainage from beneath an elastic sheet, it is also observed that the location of the contact line remains approximately pinned, as the fluid gradually drains into the thin porous layer underneath (Chase, Lai & Stone 2021; Lai et al. 2021).…”
Section: Theoretical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…On length scales considerably larger than ∼ 1 m moulins, as well as in problems where elastic flexure is more central to the geometry, elastic deformation remains important. These applications include ice shelves (e.g., Reeh et al, 2003;, large marine-terminating glaciers (Christmann et al, 2021), crevasse opening (Poinar et al, 2017), and rapid supra-and subglacial lake drainage (Dow et al, 2016(Dow et al, , 2015Lai et al, 2021).…”
Section: The Role Of Elastic Deformation In Ice Sheet Hydrologymentioning
confidence: 99%